The iguanodon's horn : how artists and scientists put a dinosaur back together again and again ... and again! - Rubin, Sean, 1986- (Clarion Books, an imprint of HarperCollins Publishers, 2024)
"Ever since mysterious bones were found in 1822, scientists and artists have tried to figure out what the creature they came from looked like. But it seems that every time they've made up their minds, someone makes a new discovery, and they have to start all over. That's only fair, though--after all, it's how knowledge advances!"-- Publisher's website